Analyzing Mixed Convection Recirculation in a Square Vented Enclosure with an Inlet-Outlet Flows using COMSOL - Ash'ari, Nur Amyliana; Muhamad Ghazali Kamardan (Enhanced Knowledge in Sciences and Technology, 2024)
This study explores mixed convection flow in a vertically square vented enclosure with heating and cooling one of the vertical walls and the other three walls were insulated by using a COMSOL. This study is performed on buoyancy supported and buoyancy resistant flows. Nondimensional governing equations were employed to analyze flow and thermal behaviors for various values of Richardson number(Ri). Streamlines and isotherms reveal significant impacts from both supporting and resisting buoyancies. Buoyancy supported flow, utilizing buoyant forces, dictates flow direction and intensity, leading to distinct streamlines and temperature contours. In contrast, buoyancy-resistant flow, influenced by opposing wall forces, generates varied flow patterns and temperature distributions.